2020
DOI: 10.1017/inp.2020.33
|View full text |Cite
|
Sign up to set email alerts
|

Cover–biomass relationships of an invasive annual grass, Bromus rubens, in the Mojave Desert

Abstract: Estimates of plant biomass are helpful for many applications in invasive plant science and management, but measuring biomass can be time consuming, costly, or impractical if destructive sampling is inappropriate. The objective of this study was to assess feasibility of developing regression equations using a fast, non-destructive measure (cover) to estimate aboveground biomass for red brome (Bromus rubens L.), a widespread non-native annual grass in the Mojave Desert, USA. At three study sites, including one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Monorope treatment and intercropping of peanuts and cowpeas with corn causes a significant increase in the growth of the plants themselves so that their retention is stronger in suppressing the growth and population of weeds. Scott (2020), reported similar results that biomass from cover crops can effectively suppress the growth of the annual weed Gulongan Poaceae. Legume biomass also increases varying soil porosity, due to increased levels of organic matter and increased activity of microorganisms such as phosphorus solubilizing bacteria and Rhizobium (Chieppa et al, 2020).…”
Section: Diversity Population and Weed Growth In Each Treatmentmentioning
confidence: 64%
See 2 more Smart Citations
“…Monorope treatment and intercropping of peanuts and cowpeas with corn causes a significant increase in the growth of the plants themselves so that their retention is stronger in suppressing the growth and population of weeds. Scott (2020), reported similar results that biomass from cover crops can effectively suppress the growth of the annual weed Gulongan Poaceae. Legume biomass also increases varying soil porosity, due to increased levels of organic matter and increased activity of microorganisms such as phosphorus solubilizing bacteria and Rhizobium (Chieppa et al, 2020).…”
Section: Diversity Population and Weed Growth In Each Treatmentmentioning
confidence: 64%
“…According to Kara et al (2020), these four weeds have high competitive power in various types of agricultural land management so they are also called invasive weeds. Scott (2020), also reported that only mulch and legume cover crop (LCC) shading pressure were effective in suppressing the population and growth of these four noxious and invasive weed species. Several gumla species are reported to be tolerant to various post-emergence herbicides (Dylan et al, 2023).…”
Section: Diversity Population and Weed Growth In Each Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in comparing means separation using cover crop biomass to cover crop cover among the various cover crop treatments, there were no changes (Figures 2 and 3). Although there are no studies comparing the correlation of cover crop biomass to cover crop cover on weed suppression, there are studies that indicate cover measurements can be used to estimate biomass (Abella 2020; Axmanova et al 2012; Chieppa et al 2020; Prabhakara et al 2015). These correlations are especially useful with the increase of remote sensing technologies (Prabhakara et al 2015) and the need to reduce the cost of vegetation sampling in remote rangeland areas (Abella 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are no studies comparing the correlation of cover crop biomass to cover crop cover on weed suppression, there are studies that indicate cover measurements can be used to estimate biomass (Abella 2020;Axmanova et al 2012;Chieppa et al 2020;Prabhakara et al 2015). These correlations are especially useful with the increase of remote sensing technologies (Prabhakara et al 2015) and the need to reduce the cost of vegetation sampling in remote rangeland areas (Abella 2020). Generally, when comparing the biomass of grass species to herbaceous plants, grass species often have more dry weight than herbaceous species if both have the same fresh weight, which may result in a bias in dry weight data indicating that a grass species might not be as suppressive to weeds as a herbaceous plant (Axmanova et al 2012).…”
Section: Cover Crop Cover and Weed Biomassmentioning
confidence: 99%